2021
DOI: 10.1111/1462-2920.15547
|View full text |Cite
|
Sign up to set email alerts
|

Interconnection of the mycobacterial heparin‐binding hemagglutinin with cholesterol degradation and heme/iron pathways identified by proximity‐dependent biotin identification inMycobacterium smegmatis

Abstract: Deciphering protein-protein interactions is a critical step in the identification and the understanding of biological mechanisms deployed by pathogenic bacteria. The development of in vivo technologies to characterize these interactions is still in its infancy, especially for bacteria whose subcellular organization is particularly complex, such as mycobacteria. In this work, we used the proximity-dependent biotin identification (BioID) to define the mycobacterial heparin-binding hemagglutinin (HbhA) interactom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…To identify proteins that interact with HsaD, each sample of biotinylated proteins from three independent biological replicates was analyzed by mass spectrometry (Table S3). From our previous study 16 and as confirmed by western blot analyses (Figure 1C), overexpression of birA alone may result in nonspecific biotinylation of mycobacterial proteins. Therefore, candidate proteins, as quantified using spectral counting, were selected by comparing their enrichment in M. smegmatis producing the bait of interest, BirA‐HsaD or HsaD‐BirA, over M. smegmatis producing BirA alone.…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…To identify proteins that interact with HsaD, each sample of biotinylated proteins from three independent biological replicates was analyzed by mass spectrometry (Table S3). From our previous study 16 and as confirmed by western blot analyses (Figure 1C), overexpression of birA alone may result in nonspecific biotinylation of mycobacterial proteins. Therefore, candidate proteins, as quantified using spectral counting, were selected by comparing their enrichment in M. smegmatis producing the bait of interest, BirA‐HsaD or HsaD‐BirA, over M. smegmatis producing BirA alone.…”
Section: Resultssupporting
confidence: 74%
“…Surprisingly, all the interactants identified with MSMEG_1634‐BirA or BirA‐MSMEG_1634 were also enriched (ratio ≥7.8) when MSMEG_1634 was produced alone (Table S6). These proteins were not overrepresented when HsaC or HsaD were produced alone (Table S4 and S5), nor in our previous study with HbhA 16 . Moreover, BkdA, BkdB, BkdC, HrpA, and MSMEG_3726 were not overrepresented in the M. smegmatis strain overproducing MSMEG_1634‐BirA (Table S6).…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations